The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1080/01652176.1986.9694031
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, renal clearance, tissue distribution, and residue aspects of sulphadimidine and its N4‐acetyl metabolite in pigs

Abstract: Pharmacokinetics and tissue distribution experiments were conducted in pigs to which sulphadimidine (SDM) was administered intravenously, orally, and intramuscularly at a dosage of 20 mg SDM/kg. SDM was acetylated extensively, but neither hydroxy metabolites nor their derivatives could be detected in plasma, edible tissues or urine. Following i.v. and two oral routes of administration, the N4-acetylsulphadimidine (N4-SDM) concentration-time curve runs parallel to that of SDM. The percentage of N4-SDM in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
6
5
0
Order By: Relevance
“…Compared with the tissue-urine ratios, the tissue-plasma ratios showed less variation. This was also observed by Nouws et al (1986a) and Randecker et al (1987).…”
Section: Liquid Chromatographic Analysessupporting
confidence: 80%
See 2 more Smart Citations
“…Compared with the tissue-urine ratios, the tissue-plasma ratios showed less variation. This was also observed by Nouws et al (1986a) and Randecker et al (1987).…”
Section: Liquid Chromatographic Analysessupporting
confidence: 80%
“…Compared with the concentrations in the tissue samples, the concentration in plasma was 2-4 times higher. This compares with the results of Nouws et al (1986a) in which they found that the sulphamethazine concentration in muscle, liver and kidney ranged from one-third to one fifth of that in plasma. It was noticeable that between the mean sulphamethazine concentrations in tissue and plasma obtained after 4 days versus 7 days drug withdrawal, no obvious differences were observed (see table 1).…”
Section: Liquid Chromatographic Analysessupporting
confidence: 76%
See 1 more Smart Citation
“…In the absence of nitrate or nitrite, the plasma concentrations of SDM and N4-acetyl-SDM were similar to those previously reported by other authors (4,8).…”
Section: Resultssupporting
confidence: 91%
“…Sulfamethazine is known to undergo metabolism to mainly form N 4 -acetyl-SM 2 in numerous species of domestic animals, including fish and humans (10)(11)(12)(13)(14). Metabolic alteration of the parent compound by fish to more polar species or to less polar species can have an impact upon bioconcentration (5), so N 4 -acetyl-SM 2 , which is less polar than SM 2 , was used as a biodegradation marker of the drug in the test organism.…”
Section: Introductionmentioning
confidence: 99%